Teaching Composition in Schools: Challenges of EFL Teachers in Post-Soviet Georgia - Jakhaia, Nino; Holmes, Kerry (Beyond Words, 2018)
Writing in foreign language classes has long been a challenge for both teachers and students. With the rise of globalization, there is an urgent need for EFL (English as a Foreign Language) teachers to help stu-dents develop writing skills needed to function effectively in a society. This article reports on the practic-es and experiences of teachers of English in Georgian schools. It discusses how writing instruction is enacted in schools; how teachers perceive their pre-service education and professional opportunities re-garding writing. The results of a qualitative analysis of teacher interviews indicate that (a) inadequate preparation at a pre-service level is a major concern for teachers; (b) absence of a unified curriculum on composition studies in schools prevents teachers from the implementation of the writing assignments in the classrooms; (c) teachers are seeking their own learning and professional growth pathways despite the lack of systematic professional development opportunities. Based on the findings, pedagogical implica-tions are discussed with the aim of enhancing the teaching and learning of written English in foreign lan-guage in Georgia and ultimately, in other foreign language contexts.